Permissionlessness - Kelsie Nabben; Michael Zargham (Internet Policy Review, 2022)
Permissionlessness" is a term often used in association with public blockchains. In this glossary entry, we explore the origins, evolution, and coexisting uses and meanings of the term "permissionless" to contextualise it. We argue that a technosocial system is deemed permissionless if it is possible to participate in the use, development, and governance of that system or infrastructure without requiring permission from an authority, by adhering to publicly stated procedures. This term is much more broadly applicable then just blockchain systems although it is relevant to decentralized systems. It can be conceptualised as a technical attribute, an ideology, and a cultural value, and links to the access, control, governance, entry and exit of an open information system.
Keywords: 300; Permission; Blockchain; Access; Governance